A Systematic Literature Review : Students’ Perception of Asynchronous and Synchronous in Learning - Ressy Novasyari; Melisa Novianty (Journal of English Language and Education, 2026)
The rapid development of digital technology has significantly transformed educational practices, particularly through the integration of synchronous and asynchronous learning modes.This article aims to conduct a systematic review of Students’ Perception of Asynchronous and Synchronous in Learning. The search strategy is based on the following keywords: " Students’ Perception of Asynchronous and Synchronous in Learning from Google Scholar. Based on the results of this article, only 7 articles analysis became. The results indicate that students generally view both learning modes positively, though for different reasons. Synchronous learning is appreciated for its real-time interaction, prompt feedback, and sense of social presence, whereas asynchronous learning is valued for its flexibility, self-paced nature, and ease of access. Most students tend to favor a blended approach that integrates the advantages of both methods. The study concludes that combining synchronous and asynchronous strategies can more effectively address diverse student needs and improve overall learning outcomes.